2015
DOI: 10.1175/jtech-d-14-00130.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Two Array Autocalibration Methods with Multifrequency HF Radar Current Measurements

Abstract: One pivotal factor affecting the accuracy of HF radar current measurements is the direction of arrival (DOA) estimation performance of the current signal. The beamforming technology or superresolution algorithm cannot always perform best in practical applications because of the phase errors existing in array channels. These phase errors, which cause uncertain estimation of DOA, lead to confused values in radial current maps. To solve this problem, this paper is focused on discussing the performances of two aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The MU method forms a cost function using the eigenstructure decomposition of single-DOA first-order sea echoes, and the phase errors in array are estimated by minimizing the cost function through an iterative procedure. For phase error calibration, the MU method and the ML approach have already been compared in the previous work [18], and that work indicates that the MU method is better than the ML approach for the MHF radar. Therefore, the MU method is adopted for comparison in this paper.…”
Section: Ship Doa Estimationmentioning
confidence: 93%
See 2 more Smart Citations
“…The MU method forms a cost function using the eigenstructure decomposition of single-DOA first-order sea echoes, and the phase errors in array are estimated by minimizing the cost function through an iterative procedure. For phase error calibration, the MU method and the ML approach have already been compared in the previous work [18], and that work indicates that the MU method is better than the ML approach for the MHF radar. Therefore, the MU method is adopted for comparison in this paper.…”
Section: Ship Doa Estimationmentioning
confidence: 93%
“…In contrast, the WavE RAdar (WERA), which takes advantage of a long receiving array, adopts the beam-forming method to steer in the desired direction. However, in practical situations, both of the approaches are negatively affected by array uncertainties [18]. Without array calibration, the beam-forming method may result in an incorrect beam with a broadened beamwidth, and the direction-finding approach would yield a spurious direction with a poor angular resolution [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a phased direction-finding HF radar system, array phase uncertainties significantly degrade the performance of estimating the azimuth of the current signal. In this paper, an auto-calibration method is utilized to estimate Φ to calibrate the array signals before estimating the current maps [31,32]. As shown in Equation (6), the number of disparate sources M must be accurately estimated before using Equation (6) to determine the DOAs of current signals.…”
Section: Signal Model and Estimation Methodsmentioning
confidence: 99%
“…Similar to the ML method, Chen et al proposed another appoach based on the multiple signal classification (MU) algotithm for amplitude and phase calibration using the reception matrices of single DOA sources [20]. Later, Zhao Chen validated and compared the ML method and the MU method, and the results showed that both methods can effectively improve the accuracy of ocean current estimation [21].…”
Section: Introductionmentioning
confidence: 99%